Determination of Phylogroups, Pathotypes and Antibiotic Resistance Profiles of E. coli Isolates from Freshwater and Wastewater in the City of Panama - Gabriela A. Rodríguez Guevara; Emmanuel Michelangelli; Juan R. Medina-Sánchez; Fermín Mejía-Meléndez; Carmen Indira Espino; José E. Moreno P.; Alex O. Martínez Torres; Jordi Querol-Audí (Pathogens)
Untreated water bodies are critical ecological niches where environmental conditions can drive the adaptive evolution of bacterial populations, enabling them to acquire new traits such as antibiotic-resistance genes. Escherichia coli is typically a commensal bacterium but can evolve into a pathogenic form, known as Diarrheagenic E. coli, responsible for both intestinal and extraintestinal diseases. This study focuses on the characterization of E. coli isolates from water samples collected from the Matasnillo River and the influence of the Juan Díaz Wastewater Treatment Plant (WWTP). While isolates from the Matasnillo River were classified as commensal, 18% of the isolates from the WWTP belonged to either phylogroups D or B2. Pathotype analysis revealed the presence of Entero-Toxigenic and Entero-Hemorrhagic E. coli in the WWTP. Moreover, Matasnillo River isolates exhibited resistance mainly to the quinolone ciprofloxacin, whereas those from the WWTP influent showed resistance to multiple broad-spectrum antibiotics. Sequencing analysis revealed the prevalence of the transmissible quinolone resistance qnrB19 among the Matasnillo River isolates and mutations conferring resistance to quinolone in gyrA, parC, and parE. These findings highlight the importance of monitoring antibiotic-resistant bacterial contamination in both freshwater and wastewater to mitigate the risk of the spread of resistant pathogens and potential epidemic outbreaks.